2016
DOI: 10.1080/15384047.2016.1250046
|View full text |Cite
|
Sign up to set email alerts
|

Belinostat and vincristine demonstrate mutually synergistic cytotoxicity associated with mitotic arrest and inhibition of polyploidy in a preclinical model of aggressive diffuse large B cell lymphoma

Abstract: Diffuse Large B-cell lymphoma (DLBCL) is an aggressive malignancy that has a 60 percent 5-year survival rate, highlighting a need for new therapeutic approaches. Histone deacetylase inhibitors (HDACi) are novel therapeutics being clinically-evaluated in combination with a variety of other drugs. However, rational selection of companion therapeutics for HDACi is difficult due to their poorly-understood, celltype specific mechanisms of action. To address this, we developed a pre-clinical model system of sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 74 publications
2
21
0
Order By: Relevance
“…Hence, combining HDACis with other chemotherapeutic agents is considered to be an effective way to enhance tumor drug sensitivity by improving the cellular efficacy and toxicity of HDACis to tumor cells [116][117][118][119][120][121][122][123][124][125] (Table 3 and Table 4). To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Specific combination strategies and their corresponding mechanisms are summarized in Table 3 [146][147][148]…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…Hence, combining HDACis with other chemotherapeutic agents is considered to be an effective way to enhance tumor drug sensitivity by improving the cellular efficacy and toxicity of HDACis to tumor cells [116][117][118][119][120][121][122][123][124][125] (Table 3 and Table 4). To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Specific combination strategies and their corresponding mechanisms are summarized in Table 3 [146][147][148]…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…Several pre-clinical tumour models have been established to further investigated the anti-tumour effect of Belinostat in various cancers [36]. As Jensen et al demonstrated in ovary cancer xenografts in mice, Belinostat decreased ovary tumour volumes [37].…”
Section: Belinostat Repressed Tumour Formation In Vivomentioning
confidence: 99%
“…Castedo et al (31) reported that polyploid tumors exhibit significant resistance to cisplatin and camptothecin. Havas et al (32) demonstrated that cells were more sensitive to chemotherapeutic drugs following polyploidization. The present study revealed that polyploid tumor cells induced by spindle poisons were less sensitive to paclitaxel, docetaxel, vincristine, oxaliplatin, 5-FU and epirubicin than the original tumor cells.…”
Section: Discussionmentioning
confidence: 99%